Inhibitory Effect of Active Substances of Lollyfish (Holothuria atra) Against the Development of Plasmodium falciparum Based on In Silico Study - Felly Moelyadi; Prawesty Diah Utami; Irmawati M. Dikman (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2020)
The high level of artemisinin resistance as the antimalarial drug makes the active substances found of lollyfish (Holothuria atra) become a very useful discovery as a new antimalarial drug. The purpose of this research is to find out the inhibitory effect of the active substances of lollyfish against the development of Plasmodium falciparum with in silico method. This is a one-shot experimental study research. Based on the test of potentially active substances of lollyfish through PubChem (https://pubchem.ncbi.nlm.nih.gov/), there are pyrogallol and catechin that have potential as the antimalarial drug. Pyrogallol, chlorogenic acid, catechin dan ascorbic acid have indirect inhibition to P. falciparum Orotidine 5-Monophosphate Decarboxylase (PfOMPDC) through carbon dioxide (CO2) and it is visualized by STITCH DB Version 5.0 (http://stitch.embl.de/). The binding affinity score of catechin, obtained from molecular docking, is higher than other substances and artemisinin. The Physicochemical and pharmacokinetic activity of the substance was predicted through SWISS ADME (http://www.swissadme.ch/index.php), while the toxicity was predicted through Pro-Tox (http://tox.charite.de/protox_II/). Catechin is a substance in lollyfish that is the safest because its lowest toxicity and very effective to be used as the antimalarial drug because of its high lethal dose 50 (LD50). Therefore, active substances in lollyfish have inhibitory effects against the development of P. falciparum based on in silico study.